2016
DOI: 10.1128/iai.00659-16
|View full text |Cite
|
Sign up to set email alerts
|

Iron Homeostasis Regulates the Genotoxicity of Escherichia coli That Produces Colibactin

Abstract: eThe genotoxin colibactin is a secondary metabolite produced by a variety of pathogenic enterobacteria. Its biosynthesis requires the enzymatic activity of the phosphopantetheinyl transferase (PPTase) ClbA. We previously showed that ClbA can also contribute to the production of siderophores. Because the biosynthesis of siderophores is regulated by iron availability, we hypothesized that iron could also modulate the production of colibactin through the transcriptional regulation of clbA. This study revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 35 publications
5
57
1
Order By: Relevance
“…Using a mutant with defective ClbP, the key enzyme implicated in pre-colibactin cleavage and generation of the active form (43), we demonstrated the colibactin-producing E. coli murine isolate NC101 is responsible for the pro-tumorigenic effect of the bacterium in Apc Min/+ ; Il10 −/− mice. Whether clbA contributes to colibactin-mediated tumorigenesis is still unclear and would need to be investigated, especially since a recent in vitro study showed that iron levels and E. coli iron sensors regulate clbA transcription and colibactin production (44). Since our studies were performed using a mono-association approach, and therefore without competitive pressure from other microorganisms, the full extent of iron acquisition on E. coli pks + induced carcinogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mutant with defective ClbP, the key enzyme implicated in pre-colibactin cleavage and generation of the active form (43), we demonstrated the colibactin-producing E. coli murine isolate NC101 is responsible for the pro-tumorigenic effect of the bacterium in Apc Min/+ ; Il10 −/− mice. Whether clbA contributes to colibactin-mediated tumorigenesis is still unclear and would need to be investigated, especially since a recent in vitro study showed that iron levels and E. coli iron sensors regulate clbA transcription and colibactin production (44). Since our studies were performed using a mono-association approach, and therefore without competitive pressure from other microorganisms, the full extent of iron acquisition on E. coli pks + induced carcinogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Shotgun metagenomic sequencing of patient stools has revealed that host glycan utilization and virulence factor genes are associated with the CRC microbiome (16) and that genes in these categories were also overexpressed in the BFϩT microbial community. Host inflammation, bacterial iron (Fur), and stress response (Hsp90 chaperone) genes have all been implicated in colibactin regulation, and all of these genes were increased in BFϩT mice (45)(46)(47). Additionally, iron acquisition genes have previously been associated with E. coli mucus colonization (48), and mucins have the capacity to induce E. coli virulence gene expression (41).…”
Section: Discussionmentioning
confidence: 99%
“…These AIEC strains colonize the mucosa by adhering to the intestinal epithelium (Darfeuille-Michaud et al, 1998), where local release of colibactin can induce DNA damage in host cells (Arthur et al, 2012;Wilson et al, 2019). Furthermore, colibactin production is coregulated with siderophore biosynthesis under iron-limiting conditions, such as intestinal inflammation (Martin et al, 2013;Ganz and Nemeth, 2015;Tronnet et al, 2016).…”
Section: Tungstate Reduces Colibactin-driven Tumorigenesismentioning
confidence: 99%